INDONESIA DALAM DUA ORDE: SEBUAH CITRA YANG RETAK - Acep Iwan Saidi (Fakultas Seni Rupa dan Desain ITB, 2007)
The unevenly distributed development can trigger a social and political conflict in local areas. The development that always supported the capitalists also created a gap, the corruption among the officials could never stop. The reformation that initially gave a hope to the people, yet it never comes true. The obvious success of reformation is only the freedom to talk, to gather, and to ally. However, the success has become a boomerang. This results in the pesimism among the intelectuals that reflects in some books. The situation has been worst by some natural disasters. Some people assume that it is closely related to the human behaviour. Both positive and negative political and social situation are unable to detach from the effect in global level, self-image, and mentality.